Hypertension in Africa: Redressing the burden of cardiovascular disease using cost-effective nonpharmacological approaches - Norton, Gavin R.; Woodiwiss, Angela J. (SA Heart Journal, 2017)
Hypertension may affect approximately one fifth or more of all adult South Africans. Despite the considerable evidence derived from economically developed countries to indicate the extent to which hypertension contributes to cardiovascular disease (CVD), it is only more recently that data has emerged from the African continent to support a contention that hypertension is the principal risk factor for CVD in African populations and that CVD accounts for a major proportion of deaths in the elderly and in younger adults in rural Africa. Active engagement in the harsh realities of managing this complex clinical trait should therefore be foremost on the minds of the healthcare sector in Africa. In this regard there are unique challenges. In the present personal review we synthesise the evidence for or against the view that at a public health level, the answer to significantly reducing the burden of CVD produced by hypertension in African populations, may lie in something as simple as generating a healthier lifestyle. In this regard, we place recent evidence obtained from South African studies of the importance of modifiable cardiovascular risk factors related to hypertension, including salt intake and obesity, in the context of previously published evidence. We highlight the very recent and the first substantive evidence derived from an African community to show that salt intake indeed contributes to a significant portion of blood pressure (BP) variability in African populations, but this effect may be hidden because the impact is largely on central (aortic) rather than brachial BP. We also discuss the increasing evidence to show that in African populations, the adverse effects of the epidemic of obesity that faces emerging communities is likely to account for a substantial proportion of cardiovascular risk not through marked effects on brachial BP, but through indirect effects by promoting the adverse effects of BP on the heart. In the present review we therefore argue that despite limited absolute effects of salt intake and obesity on brachial BP, a marked benefit could be gained by the BP effects of salt restriction and body weight reduction in African communities.